Dialectical Materialism and its Theory of Knowledge (Patan Prospective Journal, 2022)
This article explores the basic tenets of dialectical materialism and its theory of knowledge. Itis relevant to identifying the basics of dialectical materialistic philosophy and its cognitive theory. The article addresses the research problems concerning the primacy of thought or matter, the acceptance of the concept of the immutability of the cosmos or motion of matter,the source of knowledge, the validity of truth and morals, stages of cognition, and the utility of knowledge in changing the world.The article deals with the research problems through the review-based analysis of Marxist criticismsof the dialectical materialist philosophy and its cognitive theory. The article reveals that dialectical materialist philosophy believes in the primacy of matter and the motion of matter. The dialectical materialist theory of knowledge regards the objective world as the primary source of knowledge, rejects the idea of absolute and immutable truths and morals, believes in the dialectical relationship between perceptual and logical knowledge, and gives high priority to the application of the gained knowledge in changing the existing world.